La copropriété divise sous le projet de Loi 20, l’assurance et la déclaration de copropriété - Moreau, Rémi (Assurances, 1988)
When purchasing insurance for condominiums, the insurance buyer must make certain that his policy covers all potential sources of claims. The purposes of this article are to examine the new bill recently adopted by Quebec Legislature, Bill 20 and the insurance implications; to give a general description of the terms given in the Condominium Declarations; and to present a new Condominium Declaration filed by La Chambre des notaires du Québec in regard to insurance policies on building managed by the administrators and to insurance policies on personal property of the co-owners. Much literature is available on the civil law of condominiums and insurance specifications, which often reveal contradictory aspects. We welcome the standardized Condominium Declaration providing the necessary information to subscribe proper coverage.